IMPROVING MATHEMATICAL CRITICAL THINKING ABILITY THROUGH AUGMENTED REALITY-BASED LEARNING - Lilis Marina Angraini; Alzaber Alzaber; Debby Permata Sari; Fitriana Yolanda; Ilham Muhammad (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Through Augmented Reality-based learning, this study aims to improve mathematical critical thinking skills. Learning with Augmented Reality-based media in Unity 3D can be used both online and offline. This research is quantitative (quasi-experimental), with 30 students from SMPN 34 Pekanbaru class VII participating in the academic year 2022/2023. The research was conducted on triangle and quadrilateral material. The following methods were used to collect data: (1) a mathematical critical thinking ability test; (2) interviews; and (3) documentation. The test result data was statistically processed, whereas the interview and documentation data were processed descriptively. The findings revealed that students who learned using Augmented Reality media with Unity 3D improved their mathematical critical thinking skills.